INVENTARISASI NEMATODA PARASIT PADA TANAMAN, HEWAN DAN MANUSIA - Liestiana Indrayati (Universitas Lambung Mangkurat, 2017)
Pathogenic nematodas are widespread in nature, it can attack plants, animals, and humans and cause disruption to their hosts, then effect to lower quantity of plantation, yields, and livestock production and also affect to degradation of human resource quality. This paper is a systematic review that uses literature method about the inventory of nematoda parasite that attacks plants, animals and human, some method of examination and the effects that occurred by the host. The major parasite nematodas that infect the plants are Meloidogyne sp, Pratylenchut sp, and Radopholus sp., nematode in animals are Strongyloides spp., Haemonchus spp., Oesophagosomum spp., and Trichostrongyloides spp. In the fish variant, Anisakis spp, and nematode in humans are Ascaris lumbricoides, Trichuris trichiura, and hookworm. Some animal nematodas were found to attack humans whereas plant nematodas have not been reported to be found in humans or animals. Nematoda control is by anthelmintic consumption, environmental modification, personal hygiene and the use of biological agents.